PENGARUH LATIHAN BOX JUMP TERHADAP POWER OTOT TUNGKAI PADA TIM BOLA VOLI PUTRA SMP NEGERI 22 PEKANBARU - M. Hafirul M. Hafirul; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: the problem in this study is that the power of the male limb muscle of the state junior high school 22 Pekanbaru is still lacking, this can be seen from various trials and official matches and this is one of the factors causing the defeat. This type of research is a type of experimental research to see the effect of the form of training. The purpose of this study was to look at the effect of box jump training on leg muscle power in the men's volleyball team at SMP Negeri 22 Pekanbaru. The population in this study was state junior high school 22 Pekanbaru, amounting to 10 people. The sampling technique is by using total sampling, where the total population is sampled. Data collection techniques obtained from the pre-test and post test. The instrument in this study used the vertical power jump test as a tool to measure leg muscle power. The analysis was carried out using the t-test. based on data analysis and discussion, it can be concluded that there is a significant effect of box jump training on leg muscle power on the state Junior High School 22 volleyball team Pekanbaru as evidenced by the tcount of 2,384 and table of 1,895. Means Thitung> T table. At the level of ɑ = 0.05.Key Words: box jump exercise, leg muscle power